Analisis Budgetary Slack Pada Perusahaan - Khamimah Khamimah; Mochammad Bilal (Serat Acitya, 2021)
This study aims to determine the effect of accounting information systems, self esteem, locus of control, budget participation on the budgetary slack at Perusahaan. The population in this study were employees involved in budgeting in each division / department at Perusahaan, amounting to 118 people. This study uses census sampling techniques, namely the use of the entire population without having to draw the research sample as an observation unit.The results of this study show that the accounting information system and locus of control variables have a significant positive effect on the budgetary slack, while the variables of self-esteem and budget participation have no effect on the budgetary slack at Perusahaan.Keywords : Accounting Information Systems, Self Esteem, Locus of Control, Budget Participation, Budgetary Slack.